Governance and attractiveness of FDI: the case of Southern and Eastern Mediterranean countries - Mohamed, Akram Belhadj; Nidhal, Mgadmi (Open Science Journal, 2017)
This article empirically examines the role of governance in attracting FDI for a sample of ten Southern and Eastern Mediterranean countries over a 15-year period. We have approximated the attractiveness of FDI by governance through an endogenous variable called FDI in relation to GDP. The quality of these variables was tested by the positioning, dispersion and shape indicators and verified the normality of these variables by the Jarque-Berra test and the quality of linear adjustment of each variable with respect to its mean. The empirical validation of the impact of good governance in the attraction of FDI was carried out using the static Panel technique and based on the assumption of the absence of a stationarity problem for the explanatory variables of our model. Homogeneity-heterogeneity tests were used to specify the reference model and model the role of governance in the attraction of FDI by a panel with individual effects. The estimation of this model by the Within and GLS procedures yielded significant results.